Canine Ependymoma: Diagnostic Criteria and Common Pitfalls. Issue 6 (November 2019) - Miller, Andrew D.; Koehler, Jennifer W.; Donovan, Taryn A.; Stewart, Jennifer E.; Porter, Brian F.; Rissi, Daniel R.; Priestnall, Simon L.; Schulman, F. Yvonne
Reports of canine ependymoma are generally restricted to single case reports with tumor incidence estimated at 2% to 3% of primary central nervous system (CNS) tumors. While most commonly reported in the lateral ventricle, tumors can occur anywhere in the ventricular system and in extraventricular locations. Rosettes and pseudorosettes are a common histologic feature; however, these features can be mimicked by other CNS neoplasms. Thirty-seven potential ependymoma cases were identified in a retrospective database search of 8 institutions, and a histologic review of all cases was conducted. Of 37 cases, 22 candidate cases were further subjected to a consensus histologic and immunohistochemical review, and only 5 of 37 (13.5%) were conclusively identified as ependymoma. The neuroanatomic locations were the lateral ventricle (3/5), third ventricle (1/5), and mesencephalic aqueduct (1/5). Subtypes were papillary (4/5) and tanycytic (1/5). Histologic features included rosettes (5/5), pseudorosettes (5/5), ependymal canals (2/5), tanycytic differentiation (1/5), blepharoplasts (1/5), ciliated cells (1/5), and high nuclear to cytoplasmic ratio (5/5). Immunolabeling for GFAP (4/4) and CKAE1/3 (3/4) was found in pseudorosettes, rosettes, and scattered individual neoplastic cells. Diffuse but variably intense cytoplasmic S100 immunolabeling was detected in 3 of 4 cases. Olig2 intranuclear immunolabeling was observed in less than 1% of the neoplastic cells (3/3). Tumors that had pseudorosettes and mimicked ependymoma included oligodendroglioma, choroid plexus tumor, pituitary corticotroph adenoma, papillary meningioma, and suprasellar germ cell tumor. These findings indicate that canine ependymoma is an extremely rare neoplasm with histomorphologic features that overlap with other primary CNS neoplasms.